Antihyperglycemic and neuroprotective effects of Wattakaka volubilis (L.f.) Stapf root against streptozotocin induced diabetes - Hajira Banu Haroon; Anita Murali
ABSTRACT Murva is an important drug in Ayurveda. Wattakaka volubilis is used as one of the botanical sources of Murva. The aim of this study is to evaluate the effect of the alcohol extract of W. volubilis root in streptoztocin (STZ) induced diabetes and diabetic neuropathy. Diabetes mellitus (DM) was induced by the administration of STZ (45 mg/kg, i.p). DM was induced within 72 h. Diabetic animals were treated with glimepiride (0.5 mg/kg) and ethyl alcohol extract 100 and 200 mg/kg for 21 d. After determining the changes in fasting serum glucose and lipid profile, animals were further treated for a period of 15 d to determine the protective effect of extract against diabetic neuropathy. All the alcohol extract treated animals, showed a significant decrease in serum glucose level (P<0.001), and overall decrease in the severity of diabetic neuropathy. Alcohol extract of W. volubilis root showed antihyperglycemic activity and beneficial protection against diabetic neuropathy and hence can be a promising agent for treatment and prevention of diabetic neuropathy.